#### Answer

f and g are inverses of each other

#### Work Step by Step

g(f(x)) = g(x - 6) = (x-6) + 6 = x
f(g(x)) = f(x + 6) = (x + 6) - 6 = x
Since g(f(x)) = f(g(x)), f and g are inverses of each other

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

f and g are inverses of each other

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.